2021
DOI: 10.1002/cnm.3545
|View full text |Cite
|
Sign up to set email alerts
|

Growth and remodeling in the pulmonary autograft: Computational evaluation using kinematic growth models and constrained mixture theory

Abstract: Computational investigations of how soft tissues grow and remodel are gaining more and more interest and several growth and remodeling theories have been developed. Roughly, two main groups of theories for soft tissues can be distinguished: kinematic-based growth theory and theories based on constrained mixture theory. Our goal was to apply these two theories on the same experimental data. Within the experiment, a pulmonary artery was exposed to systemic conditions. The change in diameter was followed-up over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…By providing data on microstructure, mechanical properties, geometry, hemodynamics and the underlying pathways, experimental models can enable numerical simulation of autograft remodeling ( 163 , 164 ). Subsequently, the ideal conditions for remodeling, or conversely, the risk of dissection, could be identified in so-called in silico trials ( 165 ).…”
Section: Discussionmentioning
confidence: 99%
“…By providing data on microstructure, mechanical properties, geometry, hemodynamics and the underlying pathways, experimental models can enable numerical simulation of autograft remodeling ( 163 , 164 ). Subsequently, the ideal conditions for remodeling, or conversely, the risk of dissection, could be identified in so-called in silico trials ( 165 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computational simulations play a pivotal role in understanding and predicting the biomechanical factors of a wide variety of cardiovascular diseases [8, 60, 61]. In vascular medicine, knowing the precise stress and strain fields across the vascular wall is critical for understanding the formation, growth, and rupture of aneurysms [28]; for identifying high-risk regions of plaque formation, rupture, and thrombosis [48]; and for optimizing stent materials, structure, and deployment in aortic stenosis [31].…”
Section: Motivationmentioning
confidence: 99%
“…Computational models have already been used to investigate the long-term outcomes of a pulmonary autograft [18,19,20]. On the other hand, simulations have shown that both an external support and gradual loading can promote benign adaptation in vascular growth and remodeling (G&R) [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…computational model in this study relies on an axisymmetric geometry, neglecting circumferential and axial variations. Future work should overcome this limitation by integrating specific finite element geometries derived from MRI scans, as demonstrated by Vastmans et al[13,19]. Furthermore, rather than using a simplified interposition graft model of the Ross procedure, autograft data from actual heart valve experiments is already accessible in-house through Van Hoof et al[14], which should bring us closer to real-world Ross…”
mentioning
confidence: 99%